Analysis of Bantul Regency Regional Regulation Number 9 of 2021 Concerning People's Market Management - Ariyanti Luhur Tri Setyarini; Vicki Dwi Purnomo; Syukron Abdul Kadir; Benedictus Hestu Cipto Handoyo (Formosa Journal of Multidisciplinary Research, 2023)
Along with the dynamics and developments of the current situation, it shows that the existence of people's markets is increasingly left behind and unable to compete with supermarkets and shopping centers. The condition of facilities and infrastructure that is not good, internal institutions that are not optimal, services that are still traditional and changes in people's behavior that are increasingly modern are factors that make people's markets unable to compete with modern shops. Whereas within the scope of Javanese society, the power of economic activity is centered on traditional markets or people's markets. The people's market is not just a place for buying and selling, but more than that the market is related to the conception of life and socio-cultural interaction. The people's market is not only a place for economic activity, but actors can also achieve other goals, so it is necessary to provide protection for its existence. For this reason, the Bantul Regency Regional Government issued Bantul Regency Regional Regulation Number 9 of 2021 concerning Management of People's Markets. Researchers want to analyze what local wisdom exists in people's markets in Bantul Regency, and what are the Regional Regulations of Bantul Regency.